Analysis of the athlete burnout phenomenon: The past, the present and the future of athlete burnout research - Akhrem, A.; Gazdowska, Z. (Baltic Journal of Health and Physical Activity, 2016)
The paper describes traditional and alternative conceptualizations of athlete burnout, measurement instruments, the most recent studies investigating athlete burnout and potential prevention and intervention strategies.